Prática científica dos agentes nas pesquisas em estratégia nos programas stricto sensu em administração no brasil sob a ótica de bourdieu - Lima , Adriana de Sousa (2016)
The context of the scientific research can be considered as a scientific field, a social space formed by power relations between agents which accumulate scientific capital. The operation of this field produces and assumes a specific form of interest, contaminated by the knowledge of the position occupied on the hierarchies established in the field that directly influence the scientific practices choices. In this essay was aimed to understand the research agents scientific practice in strategy in the academic programs in stricto sensu in Brazil, under the Bourdieu's perspective. The research s strategy combined aspects of praxiology proposed by Bourdieu with the study technique of collective case and involved statistical analysis with a set of in-depth interviews. The main findings demonstrates that scientific practices perform as a mechanical reaction, directly determined by the conditions that precede it, adjusted by the requirements contained in the field structures. It was identified in the research, among the epistemological approaches reviewed, the predominance of studies that seek to build objective relations in which the social agent appears as a mere performer of something that is objectively programmed, that is external and the hegemony of quantitative research. Finally, it was noticed that the scientific practice of agents on research in strategy rely on the recognition of a competence which, beyond the effects it produces, provides authority and contributes to define not only game s rules but also its regularity